Rancang Bangun Pemanfaatan Alternator Sepeda Motor Automatic Untuk Sistem Genset dan Sistem Backup Power - Roman Lesmana; Romi Wiryadinata; Wahyuni Martiningsih (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2018)
Communities who live far from the reach of the source of electrical energy require a system of electricity that is easy to use and applied. One easy-to-use power plant is the electrical system on a motorcycle. The purpose of this research is to utilize the generator output voltage generated into generator set and backup power system when there is no electricity supply from PLN. The AC voltage in the alternator requires the AC regulator to DC to be connected to the inverter for the obtained voltage of 220 volts 50 Hz. Modification of the design of the utilization of alternator is done by adding windings of each coil 50 winding with 0.7 mm wire diameter. Voltage generated 31 Volts at speed 1362 rpm. For voltage and charging current at alternator source is 13 Volt 1.6 Ampere and 12 Volt 0.5 Ampere for source of regulator. Genset system on this design has a capacity of 120 Watt. 81 watt load test with 12 Volt 10 Ah battery source can last 1 hour. Installed charging system takes 6 hour with fuel consumption 1,000 ml with battery condition 20% from 10